Palms and pollen beetles: two new anthophilous beetle species of Meligethinus from Mozambique (Coleoptera: Nitidulidae: Meligethinae) - Sabatelli, Simone; Liu, Meike; Cline, Andrew Richard; Lasoń, Andrzej; Macuvele, Suzana; Muambalo, Kisimenda; Chuquela, Lucilia; Audisio, Paolo (Zootaxa, 2020)
The genus Meligethinus Grouvelle, 1906 represents a small group of pollen beetles, including some twenty species distributed from southern Palaearctic areas to northern Oriental and Afrotropical regions. All constituent species appear to be strictly associated as larvae and adults to male inflorescences of palms (Monocots: Arecaceae). Two new species of this genus (Meligethinus mondlanei sp. nov. and M. hamerlae sp. nov.) were recently discovered in southern Mozambique, and are described herein. Both are associated as larvae with male inflorescences of the widespread eastern African palm Phoenix reclinata Jacq. The two new species are compared with related taxa from central Africa. Additionally, the presence of additional species of the same genus in southern Mozambique is reported, and the local associations of several Meligethinus species are discussed.